Analysis of trade in Nigeria: The role of remittance inflows and tourism - Ojonta, Obed Ifeanyichukwu (Growth, 2025)
The importance of trade in stimulating the overall production of goods and services cannot be overemphasized across the world. Trade is crucial in an economy in terms of income generation, job creation, improvement in consumption, and poverty alleviation. Apart from the significant contributions of trade to overall growth, tourism and remittance inflows to Nigeria can be relevant in explaining the dynamics of trade. Unfortunately, the effects of tourism and remittance inflows to the Nigerian economy on trade are yet to be documented in the existing literature. Therefore, this study focuses on how the aggregate effects of tourism and remittance inflows to Nigeria influence trade in the country. The objectives of this research were adequately achieved through the support of the Ordinary Least Square (OLS) estimator and time series data spanning from 1981 to 2021. The outcome of the study revealed that tourism and remittance inflows to the country have a positive and significant impact on trade. Based on the results, it is evident that tourism and remittance inflows to Nigeria are veritable channels in encouraging trade in the country. The study recommends that the government promote policies supporting remittance and tourism to achieve maximum trade performance in Nigeria through legislative instruments.